Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 13 - Cumulative Review - Page 969: 35



Work Step by Step

$\sqrt[3] (-64)=\sqrt[3] (-4)^{3}=(-4)^{3\times\frac{1}{3}}=(-4)^{1}=-4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.